The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2147/ppa.s351771
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patient-Reported Experience Measures (PREMs) Regarding the Policies Implemented to Contain the Spread of Sars-CoV-2 and Vaccination Campaign at Veneto Institute of Oncology

Abstract: The SARS-CoV-2 spread has impacted Healthcare systems. COVID-19 pandemic has had consequences for patients with cancer, being associated with delays in diagnosis, in treatment And follow-up care, increase in overall infection rates and higher mortality. A survey on COVID-19 and a vaccination-questionnaire were developed at different times of the outbreak, to evaluate cancer patient-reported experience measures (PREMs) on the policies implemented to reduce the infection from SARS-CoV-2 and on the timing and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Measuring patients' satisfaction is necessary to improve the provision of SCOC 17 . Involving patients in the organization reframing of services can lead to authentic personalized medicine, and help healthcare providers making choices which are both informed and consistent with patients' needs 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring patients' satisfaction is necessary to improve the provision of SCOC 17 . Involving patients in the organization reframing of services can lead to authentic personalized medicine, and help healthcare providers making choices which are both informed and consistent with patients' needs 18 …”
Section: Discussionmentioning
confidence: 99%
“…17 Involving patients in the organization reframing of services can lead to authentic personalized medicine, and help healthcare providers making choices which are both informed and consistent with patients' needs. 18 Patients with advanced cancer have a high burden of unmet needs, with special regard to symptoms control, psychological and emotional support and communication. 19,20 There is evidence showing that dissatisfaction with medical information and communication is associated with anxiety and depression which, in turn, contribute to the global burden of disability in patients with advanced cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We found that with proper patient education, vaccination and clinical screening for symptoms or viral exposure, we maintained the outpatient clinical arena largely free of SARS-CoV-2, 12 with good patient's satisfaction. 26 Moreover, given the rapid and benign evolution of the infection, we recommend considering continuing with systemic anticancer treatment, especially in patients undergoing treatment with curative intent.…”
Section: Introductionmentioning
confidence: 99%